La reivindicación de las barras bravas a través de un análisis semiótico caso sur oscura - Pinta Padilla, Nathaly Esthefania (2017)
The present project was carried out with the purpose of understanding the semiotic and social dynamics that are developed within the wild bars, to contribute to the debate and to discourage the opinions that are presente don a daily basis. The problematic of this project deals with identification codes with which the fans of the "Southern Dark Quito" (SOUIO) are handled, being they by political, economic, gender or the geography, in addition, it is taken in account the problem of society's rejection of this movement, therefore, the general objective is to identify the semiotic codes with which social relations, ties and bonds of the young supporters of the "Sur Oscura Quito" fans are built, for it is fulfillment proposes different specific objectives that will allow diagnose the reality in which the fans developed, in addition, the project is based on theories that will help to understand the problematic of investigation. To obtain real data to justify the project, a mixed methodology has been applied, that is, inductive and deductive….